O82 A phase 1 dose escalation study of PRS-343, a HER2/4–1BB bispecific molecule, in patients with HER2-positive malignancies. (15th April 2020) - Piha-Paul, Sarina; Bendell, Johanna; Tolcher, Anthony; Hurvitz, Sara; Patnaik, Amita; Shroff, Rachna; Pohlmann, Paula; Zettl, Markus; Hahn, Noah; Krishnamurthy, Anuradha; Duerr, Manuela; Mei, Jian; et al.
Abstract : Background: Anticalin® proteins are recombinantly engineered human proteins based on lipocalins. PRS-343 is a first-in-class bispecific antibody-Anticalin fusion protein targeting the oncogenic tumor antigen HER2 and the costimulatory immune receptor 4-1BB on T and other immune cells. Here, we report the results of a phase 1 single-agent dose escalation trial in patients with HER2+ solid tumors. Methods: PRS-343 has been evaluated in sequential dose cohorts from 0.0005 to 8 mg/kg i.v. Doses were administered Q3W and the 8 mg/kg dose was also given Q2W. An accelerated titration design was utilized for the initial dose escalation followed by a modified 3+3 design and the option to back-fill cohorts. Dose-limiting toxicities (DLTs) were reported during the first cycle of each schedule. The primary study objectives include the safety profile and RP2D of PRS-343. Secondary objectives include ORR and DCR, PD biomarker response and PK profile. PD response was assessed in tumor biopsies (CD8+ T cell IHC) pre- and post- PRS-343 treatment. Results: 51 patients (median age 61.2 years, 61% female, 82% caucasian, 57% with more than three lines of prior therapy) with a variety of solid tumor indications [gastric/GEJ (n=19); BC (n=12); gynecological cancer (n=6); CRC (n=5); BTC (n=4); UC (n=2); melanoma, pancreatic and salivary duct (n=1 each)] have been treated with PRS-343. Based on pharmacokinetic analyses and observed kinetics of the CD8+ T cell expansion post-treatment, the low end of the active dose range is considered 2.5 mg/kg. 19 patients treated at active dose levels before the data cut-off on 09-06-2019 were evaluable for response [DCR 58% (11% confirmed PR) as per RECIST 1.1]. At the active doses, we observed significant and pronounced post-treatment expansion of CD8+ T cells particularly in the tumor nests, consistent with the MoA of PRS-343, while there was no increase in the doses below 2.5 mg/kg. The post-treatment expansion of CD8+ T cells was more pronounced in patients with a confirmed PR or prolonged SD. PRS-343 was very well tolerated, with no SAEs reported. The most frequent TRAEs were fatigue (9%), chills (6%) and diarrhea (5%) of mild to moderate severity. None qualified as a DLT. Conclusions: PRS-343 is the first molecule of its kind to demonstrate encouraging evidence of safety and clinical benefit with a correlative PD effect in a heavily pre-treated population. These initial data suggest that PRS-343, the first 4-1BB bispecific to enter clinical development, merits further investigation in clinical trials. Trial Registration: NCT03330561